Purification, physicochemical and funtional characterisation of Glossina Morsitans centralis fibrinolysins. - Endege, W.O. (University of Nairobi, 1987)
Tsetse flies are blood-sucking insects. The ability to keep their blood meal in an anticoagulated state by means of anticoagulant(s), fibrinogenuse(s), fibrinolysin(s) or plasminogen activator like activities is essential to their survival. In this investigation tsetse midgut fibrinolytic activities have been characterised. Five proteases that hydrolyse Tosyl-Gly-Pro-Arg-pnitroanilide (chromozym-TH) at different rates, were identified in tsetse midgut extracts and four of them purified to apparent homogeneity using anion-exchange chromatography on DE-52 cellulose followed by isoe1ectric focusing. Assays using radio-labelled fibrinogen and fibrin were developed. These showed that two of the proteases with highest fibrinogenolytic activity (P3 and P4) had exo- and endopeptidase- like activities respectively. The two enzymes had pIs of 6.0 and 5.3 on isoelectric focusing and Mr of 26 and 24.5 kDa on sodium dodecyl sulphate (SDS) denaturing gels, respectively. They appeared electrophoretica1ly homogeneous as judged by SDS polyacrylamide electrophoresis (PAGE). The two enzymes seem to digest fibrinogen and fibrin at different sites but within the same domains as does bovine plasmin, a classical fibrinolysin. Tsetse fibrinolysin P3 initially generates very low molecular mass products (range 14-20 kDa), but after extended incubation times it starts generating a br.eakdown product of apparent ftlr94 kDa. Fibrinolysin P4 also produced the 94 kDa fragment and another fragment of 42 kDa, as well as larger intermediate breakdown products of approximate Mr 160and 240 kDa. The two tsetse fibrinolysins have a pH optimum around 8.0. Inhibition studies showed that these two tsetse fibrinolysins were serine proteases since diisopropylfluorophosphate (DFP) completely abolished their hydrolytic activity towards Tosyl-Gly-Pro-Arg-pNA. These enzymes had trypsin-like specificity since TLCK, a chloromethyl ketone inhibitor with trypsin-like enzyme-specificity, inhibited 75% of their activity towards this tripeptide substrate. This compared with only 25% inhibition of these enzymes by TPCK, an inhibitor of chymotrypsin-like proteases. Their trypsin-like specificity was also suggested by trypsin specific chromogenic p-nitroanilide substrates, which these enzymes hydrolysed rapidly, and additionally by the inhibition of the enzymes by aprotinin. A thermolability study showed a biphasic curve with gradual loss of activity upto 500C after which there was a precipitious loss of activity with further increase in temperature. An antibody against fibrinolysin p4 was raised in rabbits. This antibody reacted with~fibrinolysins P3 and P4 thus suggesting that the two share some common antigenic determinants. Fab fragments made from the purified immune IgG did not inhibit in vitro hydrolysis of the Tosyl-Gly-Pro-Arg-PNA thus suggesting that these antibodies we~e not directed to the active sites of the enzymes.